SERINC5 counters retroviruses and non-retroviruses - Jinghua Yu; Jinghua Yu; Jinghua Yu; Chunyu Liu; Xinglong Qu; Xinglin Gao; Yue Liu (Frontiers in Cellular and Infection Microbiology)
SERINC5 (serine incorporator 5), a member of the serine incorporator family, has been identified as a retrovirus restriction factor that inhibits the fusion of virions with the plasma membrane, thus blocking the release of the viral core into target cells and subsequently attenuating viral infectivity. Several viruses, such as human immunodeficiency virus (HIV), murine leukemia virus (MLV), and equine infectious anemia virus (EIAV), have evolved mechanisms to antagonize the host protein SERINC5 through HIV Nef, MLV glycosylated Gag, and the EIAV S2 protein. These viral proteins degrade SERINC5 on the cell surface through the endolysosomal system. In addition to its direct antiviral ability, SERINC5 also modulates immunity to inhibit the replication of retroviruses and nonretroviruses. This review summarizes the interaction between SERINC5 and viral replication, providing a promising avenue for fighting viral diseases.